Sustainable External Debt Levels: Estimates for Selected Asian Countries - Mariano, Roberto S. (Institutional Knowledge at Singapore Management University, 2005)
High ratios of external debt to GDP in selected Asian countries have contributed to the initiation, propagation, and severity of the financial and economic crises in recent years, reflecting runaway fiscal deficits and excessive foreign borrowing by the private sector. Applying the formal framework proposed by Villanueva (2003) to a selected group of Asian countries, the research estimates the external debt thresholds beyond which further debt accumulation will have negative effects on growth and will become unsustainable. The framework is an extension of the standard neoclassical growth model that incorporates global capital markets. ‘Sustainability’ is measured in terms of the steady-state ratio of the stock of external debt to GDP, as functions of real world interest rates, risk spreads and their responsiveness to external debt burdens and market perceptions of country risk, marginal propensities to save out of national disposable income and foreign borrowing, rates of technical change, and parameters of the production function. The major policy implications are that in the long run, fiscal consolidation and the promotion of private saving are critical, and that reliance on foreign saving in a globalized financial world has limits, particularly when the risk spreads are positively correlated with rising external debt levels.